Cohesin reconstitution and homologous recombination repair of DNA double-strand breaks in late mitosis - Ayra Plasencia, Jessel; Medina-Suárez, Sara; Hernández-Carralero, Esperanza; García-Luis, Jonay; Symington, Lorraine S; Machín, Félix (eLife, 2025)
The cohesin complex maintains sister chromatid cohesion from S phase to anaphase onset. Cohesin also plays roles in chromosome structure and DNA repair. In yeast, the cohesin subunit Scc1 is cleaved at anaphase onset to allow segregation in an orderly manner, although some residual cohesin subunits remain to maintain chromosome structure. Efficient DNA double-strand break (DSB) repair by homologous recombination (HR) with the sister chromatid also depends on cohesin. Here, we have examined the role of residual cohesin in DSB repair in telophase (late mitosis). We have found that Scc1 returns in telophase after DSBs and that it partially reconstitutes a chromatin-bound cohesin complex with Smc1 and an acetylated pool of Smc3 after a single HO-induced DSB at the MAT locus. However, this new cohesin is neither required for the HR-driven MAT switching nor binds to the MAT locus after the DSB.
Keywords: DNA double-strand break; anaphase; cohesin; Scc1/Mcd1; homologous recombination; MAT switching